2009
DOI: 10.1002/lsm.20741
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for recurrence of vaginal intraepithelial neoplasia in the vaginal vault after laser vaporization

Abstract: Laser vaporization may be a feasible method for the treatment of VAIN in the vaginal vault after hysterectomy. However, age (< or =48 years) and VAIN III in the vaginal vault before laser vaporization should be considered as risk factors for recurrence after laser vaporization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 22 publications
(31 reference statements)
3
13
0
1
Order By: Relevance
“…First, the proportion (64.3%) of patients with low‐grade lesion (VAIN I) in the former was higher than the proportion (18.2%) of the latter, which was consistent with many studies, indicating that the grade of VAIN increased with the severity of CIN . Second, it was reported that high‐risk HPV infection may be associated with advanced‐disease VAIN . In our study, at the time of diagnosis of VAIN, the proportion of high‐risk HPV infection was 82.1% in VAIN women post‐hysterectomy due to CIN and 100% in VAIN women post‐hysterectomy due to CC.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…First, the proportion (64.3%) of patients with low‐grade lesion (VAIN I) in the former was higher than the proportion (18.2%) of the latter, which was consistent with many studies, indicating that the grade of VAIN increased with the severity of CIN . Second, it was reported that high‐risk HPV infection may be associated with advanced‐disease VAIN . In our study, at the time of diagnosis of VAIN, the proportion of high‐risk HPV infection was 82.1% in VAIN women post‐hysterectomy due to CIN and 100% in VAIN women post‐hysterectomy due to CC.…”
Section: Discussionsupporting
confidence: 90%
“…For the treatment of VAIN after hysterectomy, laser vaporization or vaginectomy may be more effective for VAIN . Although vaginectomy is a radical treatment of VAIN, it causes significant complications, such as vesicovaginal and rectovaginal fistulas, the need for skin grafts, and it is not ideal for women who are sexually active because of its impact on psychosexual well‐being.…”
Section: Introductionmentioning
confidence: 99%
“…Efficacy rates have been similar to that of laser vaporisation also with regard to recurrence rates, but adverse effects including chronic ulcerations after 5‐fluorourasil have been more common . Previous studies have reported 46–86% cure rates after one laser vaporisation treatment round . Our result of 70% complete histological regression with imiquimod and 90% with laser treated patients can be considered equally effective as conventional laser vaporisation.…”
Section: Discussionsupporting
confidence: 57%
“…Risk factors for relapse of VAIN have been shown to be persistent hrHPV infection and the severity of VAIN. 11,13,22,26 HPV clearance could decrease the risk of recurrent disease. HPV persistence after laser vaporisation has been in previous studies 23-62%.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, more than 50 % of the women had abnormal cytology or suspicious colposcopical findings following treatment. Other studies showed similar [8] or slightly lower values [15]. A large study that evaluated 411 women with high-grade VIN and VAIN found recurrence after treatment with CO 2 laser evaporation or surgical excision in almost 30 % [9].…”
Section: Discussionmentioning
confidence: 94%